Manajemen Pengembangan Ekoliterasi Anak Usia Dini Melalui Program Green School - Mila Syahlaena (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2026)
In the midst of increasing environmental damage, environmental education for early childhood is very urgent because they are at a sensitive time in forming habits of caring for nature. This study aims to tell how the management of the Green School program at Tahfidz MQA Kindergarten is carried out and how it impacts the development of children's ecoliteration. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. Data analysis is carried out using an interactive analysis model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the green school program at Tahfidz MQA Kindergarten is implemented in a sustainable manner and integrated into the school culture through daily activities such as saving water, sorting waste, and caring for plants. This consistent implementation encourages the development of children's ecoliteracy skills, including basic environmental knowledge, plant care skills, waste management skills, awareness of resource management, and caring for nature. This program that is integrated in routine and learning has proven to be effective in forming ecological habits from an early age.